Seminal vesicle secretion IV gene: allelic difference due to a series of 20-base-pair direct tandem repeats within an intron. - Harris, S E (1983)
The rat seminal vesicle secretion IV (SVS IV) gene was isolated from a lambda Charon 4A library. The SVS IV gene transcription unit was found to be on one 3.3-kilobase (kb) EcoRI fragment. Restriction mapping and DNA sequence analysis demonstrated that the entire length of the SVS IV transcription unit is 1,930 base pairs (bp) and contains two introns. The 3.3-kb EcoRI fragment contains 144 bp of 5'-flanking region. At -113 bp from the presumed transcription initiation site an interesting structure with perfect dyad symmetry is noted. In another lambda clone, a 3.5-kb EcoRI fragment was isolated that contains the SVS IV gene and was shown to be identical to the 3.3-kb EcoRI fragment except for 180 bp of DNA in the second intron. The extra DNA consists of several (8-10) 20-bp tandem repeats flanked on each side by seven or eight copies of this same 20-bp repeat. Fisher X Sprague-Dawley hybrid rats, which contain both the EcoRI 3.5-kb form and the 3.3-kb form of the SVS IV gene, were crossed with each other. Analysis of the F1 generation demonstrated that the presence or absence of the 180-bp intronic insertion in the SVS IV gene defines an allelic difference. This report also presents the DNA sequence of the transcription unit and flanking regions of the SVS IV gene.